2020
DOI: 10.1620/tjem.252.209
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Follicular Thyroid Neoplasm with Papillary-Like Nuclear Features: From Echography to Genetic Profile

Abstract: In thyroid pathology, the great variety of types and the wide range of aggressiveness of thyroid cancers complicate both diagnosis and management. In 2016, a subset of noninvasive encapsulated follicular variant of papillary thyroid carcinoma was reclassified as noninvasive follicular thyroid tumor with papillarylike nuclear features (NIFTP) to reduce overtreatment of this low-risk tumor that follows a benign course after surgery. Starting from a paradigmatic clinical case, in this short review, we will summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…In the same histological background in regard NIFTP, this new entity must be differentiated histologically rather than cytologically from other thyroid neoplasms as follicular adenoma, EFVPTC, FT-UMP (follicular tumor of uncertain malignant potential), WDT-UMP (well-differentiated tumor with uncertain malignant potential) as well as recently introduced borderline tumor with papillary structure "NEPRAS,". The above pitfalls can be solved by the application of the diagnostic parameters of NIFTP, the diagnosis will be straightforward [44,10]. A study by Hirokawa and coworkers 2020 showed that in a Japanese retrospective case series, the peculiar differential diagnosis of NIFTP is follicular adenoma rather than other neoplasms [45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the same histological background in regard NIFTP, this new entity must be differentiated histologically rather than cytologically from other thyroid neoplasms as follicular adenoma, EFVPTC, FT-UMP (follicular tumor of uncertain malignant potential), WDT-UMP (well-differentiated tumor with uncertain malignant potential) as well as recently introduced borderline tumor with papillary structure "NEPRAS,". The above pitfalls can be solved by the application of the diagnostic parameters of NIFTP, the diagnosis will be straightforward [44,10]. A study by Hirokawa and coworkers 2020 showed that in a Japanese retrospective case series, the peculiar differential diagnosis of NIFTP is follicular adenoma rather than other neoplasms [45].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally a recent international multidisciplinary collaborative group agreed about this variant. Finally, this new entity was agreed by American Thyroid Association in their treatment recommendations [4][5][6][7][8][9][10][11]. By new nomenclature of NIFTP, the term thyroid carcinoma is avoided so, over-diagnosis and overtreatment of tumors with indolent biological behavior and a good prognosis will become clear and carries an excellent congratulation for patients [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a preoperative NIFTP diagnosis is extremely difficult, as they do not show peculiar ultrasound (US) nor cyto-morphological features [ 12 ]. On fine-needle aspiration (FNA), they are mostly classified as indeterminate nodules [ 13 ].…”
Section: Introductionmentioning
confidence: 99%